Former Yugoslav Republic of Macedonia : Selected Issues. (IMF Staff Country Reports; Country Report, 2011)
This paper asks 1) whether reliance on Eurobond financing over the medium term is consistent with sound debt management policy and 2) whether Macedonia can reasonably expect Eurobond borrowing costs to fall in the future. The main conclusions are that Eurobond financing appears justified in the near term but over a longer horizon, the country should seek to develop domestic debt markets as a complementary funding source. For 2011-12, the government plans to fully finance its fiscal deficits though Eurobond issues.